Geochemical Study on the Annual Variation of Oxygen Isotope and Chemical Composition of Groundwater in the Sho River Alluvium Fan, Toyama, Japan, as an Investigation of Selected Qualitative Aspects of Efficient Utilization of Groundwater Heat - Kaname Iwatake; Akira Ueda (Geosciences, 2021)
Seasonal variations of water temperature, electric conductivity, and oxygen isotope and chemical composition of shallow groundwaters and river waters were determined in the Sho River alluvial fan, western Toyama Prefecture, Japan, to examine groundwater heat utilization for indoor climate control. Samples were collected at 31 sites every 2 months for 1 year and at 11 representative sites monthly. In addition, the results of monthly precipitation amount and oxygen isotope composition of precipitation collected within the region during the same period were also taken into account. The sources of the shallow groundwaters are a mixture of river water and precipitation. The contribution of precipitation to groundwater is generally small along the Sho River but reaches as much as 80% along the Oyabe River and in the south and west of the alluvial fan. Though the origin of the groundwater differs regionally, water temperature is fixed at around 15 °C throughout the year in the northern part of the alluvial fan, and open-type ground source heat pump systems can be used for cooling and heating there, if adequate quantitative aquifer properties (exploitable groundwater amounts) are present.